Sejarah Pemikiran Ekonomi Islam Pada Masa Daulah Bani Umayyah dan Bani Abbasiyah - Huda, Muhammad Nurul (Universitas Indraprasta PGRI, 2021)
This article is the result of an analysis of economic history in the past which is to answer economic problems during the Umayyad and Abasiyyah Daulah,economic activities carried out during the Daulah Bani Umayyah and BaniAbasiyyah. This research uses the Historical Method by using secondarysources originating from December. which literature has been previouslyreviewed and analyzed. While in the approach the writer uses a historicalapproach. This approach is used by the author in order to reveal the economicproblems of the Umayyad and Abasiyyah Bani. From the research results, itcan be seen that the development of Islamic economics in the Umayyad andAbbasid dynasties was an economic policy formed based on the ijtihad of thefuqoha and ulama as a consequence of the increasingly distant time spanbetween the Prophet's life and the reign. The abbasiyah caliph or the dynasty ofthe children of the abbot, as said to continue the rule of the Umayyad dynasty.His power lasted a long time. During the Abbasiyah dynasty in power wherethe patterns of government applied varied according to political, social andcultural changes. Keywords: Economy, Caliph, Islam